Socially Responsible Funds and Traditional Energy Commodities: A Diversification Perspective for Investments - Rehman, Mobeen Ur; Kashif, Muhammad; Naifar, Nader; Shahzad, Syed Jawad Hussain (Frontiers in Environmental Science, 2021)
Our work examines relationship between socially responsible funds and traditional energy market over daily returns data ranging from December 2015 – April 2019. To measure the connectedness between both markets, we apply quantile cross-spectral analysis to measure returns correlation under different market conditions in the short-, medium-, and long-run. Our results highlight that correlation based on different quantile distribution yield different investment opportunities. In the short-run, investors can benefit by diversifying assets under extreme market conditions. No significant diversification opportunities are available in medium- and long-run periods. Our findings provide implications for individual investors making investments under different horizons and dynamic market conditions.